Natural rubber/styrene butadiene rubber/recycled nitrile glove (NR/SBR/rNBRg) ternary blend: Curing characteristics and swelling test - Nik Zakaria, Nik Yahya (Trans Tech Publications, 2014)
Link to publisher's homepage at http://www.ttp.net/